2009
DOI: 10.1002/chem.200900549
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Defined Potassium‐Mediated Zincation of Pyridine and 4‐R‐Substituted Pyridines (R=Et, iPr, tBu, Ph, and Me2N) by Using Dialkyl–TMP–Zincate Bases

Abstract: Two potassium–dialkyl–TMP–zincate bases [(pmdeta)K(μ-Et)(μ-tmp)Zn(Et)] (1) (PMDETA=N,N,N′,N′′,N′′-pentamethyldiethylenetriamine, TMP=2,2,6,6-tetramethylpiperidide), and [(pmdeta)K(μ-nBu)(μ-tmp)Zn(nBu)] (2), have been synthesized by a simple co-complexation procedure. Treatment of 1 with a series of substituted 4-R-pyridines (R=Me2N, H, Et, iPr, tBu, and Ph) gave 2-zincated products of the general formula [{2-Zn(Et)2-μ-4-R-C5H3N}2⋅2{K(pmdeta)}] (3–8, respectively) in isolated crystalline yields of 53, 16, 7, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…Am ixture of compounds is observed by in situ 1 H and 13 (7), N2-Li1 2.046 (7), O1-Li1A1.964 (7), O1-Li1 1.980 (7);C py -Al1-C py 104.28 (15),C py -Al1-O1101.41 (14) in the chemical shifts of C2 of the 2-py group in the 13 CNMR spectrumc ompared to 5 suggested that at least some transfer of the 2-py group onto Zn 2 + had occurred. [19] This was confirmed by the isolation of af ew crystals of dimeric [LiZn(6-Brpy) 3 ] 2 (6)f rom the NMR-scale reaction and their structural characterization (see Figure 7). Compound 6 consists of ad imeric zincate [Zn(6-Br-2-py) 3 ] 2 2À dianion ion-paired with two Li + cations, in which full transfer of the 6-Br-2-py groups has occurred from Al to Zn.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Am ixture of compounds is observed by in situ 1 H and 13 (7), N2-Li1 2.046 (7), O1-Li1A1.964 (7), O1-Li1 1.980 (7);C py -Al1-C py 104.28 (15),C py -Al1-O1101.41 (14) in the chemical shifts of C2 of the 2-py group in the 13 CNMR spectrumc ompared to 5 suggested that at least some transfer of the 2-py group onto Zn 2 + had occurred. [19] This was confirmed by the isolation of af ew crystals of dimeric [LiZn(6-Brpy) 3 ] 2 (6)f rom the NMR-scale reaction and their structural characterization (see Figure 7). Compound 6 consists of ad imeric zincate [Zn(6-Br-2-py) 3 ] 2 2À dianion ion-paired with two Li + cations, in which full transfer of the 6-Br-2-py groups has occurred from Al to Zn.…”
Section: Resultsmentioning
confidence: 71%
“…However, the ca. 20 ppm increase in the chemical shifts of C2 of the 2‐py group in the 13 C NMR spectrum compared to 5 suggested that at least some transfer of the 2‐py group onto Zn 2+ had occurred 19. This was confirmed by the isolation of a few crystals of dimeric [LiZn(6‐Br‐py) 3 ] 2 ( 6 ) from the NMR‐scale reaction and their structural characterization (see Figure 7).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…By using ac hiral potassium complex prepared from trimethylsilylmethyl potassium (KCH 2 SiMe 3 ) [22] and chiral diamine L, [23] the addition reaction of toluene with 1b proceeded in high yield with significant enantioselectivity (Scheme 2). By using ac hiral potassium complex prepared from trimethylsilylmethyl potassium (KCH 2 SiMe 3 ) [22] and chiral diamine L, [23] the addition reaction of toluene with 1b proceeded in high yield with significant enantioselectivity (Scheme 2).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…While lithium complexes are often smaller (and consequently more soluble) oligomers, heavier sodium and potassium derivatives have a tendency to give larger insoluble polymers; for example, hexameric LiCH 2 SiMe 3 [10] is commercially available as a hexane solution yet its K congener is insoluble in the same medium. [11] Whereas judicious choice of anion and Lewis donor can disrupt the polymerization of lithium species, it is much more arduous to do so with Na or K complexes of simple organic anions. [12] As a consequence of this there is a paucity of successful structural studies pertaining to simple organopotassium complexes in the literature.…”
mentioning
confidence: 99%